Project-based learning and student motivation at SMB Dharma Virya Oku Timur - Sudhar Wati; Wistina Seneru; Vike Aprilianin Marwintaria Saputri (International Journal of Science and Applied Science: Conference Series, 2025)
This study aims to determine the effect of project-based learning (PBL) on student learning motivation at SMB Dharma Virya OKU Timur. The problem addressed in this study is based on the low learning motivation of students due to the dominance of conventional learning methods. The research was conducted at SMB Dharma Virya Oku Timur using a quantitative survey method, in which students were divided into a group that applied PBL and a control group that used conventional methods. The research instrument was a learning motivation questionnaire that had been tested for validity and reliability. The results showed that there was a significant increase in learning motivation among students who participated in project-based learning compared to the control group. The application of PBL contributed significantly to increasing student motivation, activity, and learning achievement. Teachers can also implement several strategies to minimize shortcomings, such as providing a clear structure and sufficient basic knowledge before starting a project, as well as monitoring student progress regularly. The success of student learning can be determined by the motivation that the students themselves have. Students who have high learning motivation tend to have high achievement, whereas students who have low learning motivation will have low learning achievement. The level of motivation can determine the level of effort and enthusiasm a person has for an activity. Thus, the Project-Based Learning model can be an effective and meaningful learning approach for students. Therefore, it can be concluded that project-based learning is effective in increasing student learning motivation and can be used as an alternative learning strategy in schools.